CRM Practices In Malaysian Mobile Telecommunication Service Industry - Ting, Lo Wan (2001)
The main aim of this paper is to identify the CRM practices of each Malaysian mobile telecommunication service providers and furthermore find out the customers' perception towards their CRM efforts.